1999
DOI: 10.1007/s002449900460
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicity of Glyphosate and Several Glyphosate Formulations to Four Species of Southwestern Australian Frogs

Abstract: The acute toxicity of technical-grade glyphosate acid, glyphosate isopropylamine, and three glyphosate formulations was determined for adults of one species and tadpoles of four species of southwestern Australian frogs in 48-h static/renewal tests. The 48-h LC50 values for Roundup(R) Herbicide (MON 2139) tested against tadpoles of Crinia insignifera, Heleioporus eyrei, Limnodynastes dorsalis, and Litoria moorei ranged between 8.1 and 32.2 mg/L (2.9 and 11.6 mg/L glyphosate acid equivalent [AE]), while the 48-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
253
1
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(273 citation statements)
references
References 17 publications
11
253
1
8
Order By: Relevance
“…Effects of glyphosate and commercial formulations on plants and algae have been reported in the literature (Sáenz et al, 1997;Ma et al, 2002;Cedergreen and Streibig, 2005;Agritox, 2006;Ma et al, 2006;Pettersson and Ekelund, 2006;Toxnet, 2006). The toxicity of glyphosate has also been studied in a range of organisms including fish (salmon, trout, catfish), aquatic invertebrates (daphnids, midge's larvae) and ciliated protozoa (T. thermophila, Ichthyophthirius multililiis) (Folmar et al, 1979;Servizi et al, 1987;Mann and Bidwell, 1999;Everett and Dickerson, 2003;Agritox, 2006). A few values have been reported for ecotoxicity of the metabolite AMPA on fish, algae, and invertebrates (Agritox, 2006), indicating that AMPA is less toxic than glyphosate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of glyphosate and commercial formulations on plants and algae have been reported in the literature (Sáenz et al, 1997;Ma et al, 2002;Cedergreen and Streibig, 2005;Agritox, 2006;Ma et al, 2006;Pettersson and Ekelund, 2006;Toxnet, 2006). The toxicity of glyphosate has also been studied in a range of organisms including fish (salmon, trout, catfish), aquatic invertebrates (daphnids, midge's larvae) and ciliated protozoa (T. thermophila, Ichthyophthirius multililiis) (Folmar et al, 1979;Servizi et al, 1987;Mann and Bidwell, 1999;Everett and Dickerson, 2003;Agritox, 2006). A few values have been reported for ecotoxicity of the metabolite AMPA on fish, algae, and invertebrates (Agritox, 2006), indicating that AMPA is less toxic than glyphosate.…”
Section: Discussionmentioning
confidence: 99%
“…Ecotoxicological values have been determined for glyphosate and AMPA (Agritox, 2006;Toxnet, 2006). Multiple studies have found that commercial glyphosate-based formulations are more toxic to aquatic organisms than glyphosate itself (Folmar et al, 1979;Servizi et al, 1987;Mann and Bidwell, 1999;Everett and Dickerson, 2003;Tsui and Chu, 2003) because of the surfactants present in the formulations. AMPA is thought to be equally or less toxic than glyphosate (Carlisle and Trevors, 1988;Giesy et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A caracterização de um bioindicador requer uma série de informações sobre sensibilidade, ciclo reprodutivo, facilidade de operação e custo de otimização (Mann & Bidwell, 1999).…”
Section: Introductionunclassified
“…Devido à acentuada sensibilidade, as macrófitas aquáticas são utilizadas nos estudos ecotoxicológicos com herbicidas (Mann & Bidwell, 1999). De acordo com Lumpkin & Pluckneet (1980), Azolla sp.…”
Section: Introductionunclassified
“…Por exemplo, glifosato é o herbicida mais usado no mundo, em termos de volume (20%; ARMAS et al, 2005), mas poucos são os estudos que avaliam a toxicidade aguda do ingrediente ativo glifosato (BIDWELL & GORRIE, 1995;MANN & BIDWELL, 1999;LAJMANOVICH et al, 2003;HOWE et al, 2004;BERNAL et al, 2009 Além da escassez de trabalhos que avaliem a toxicidade aguda dos ingredientes ativos investigados nesta dissertação a anfíbios, diversos fatores influenciam de forma significativa a toxicidade de compostos e sua comparação, como o tempo de exposição, o regime de renovação das soluções-teste, a forma de manipulação do composto -se ingredientes ativo ou se formulação, e o estágio de desenvolvimento inicial dos indivíduos, entre outros. Por todos estes motivos, esta revisão evidencia, mais uma vez, a importância da utilização de experimentos ecotoxicológicos padronizados de exposição aguda como ferramenta para a avaliação da variação interespecífica da sensibilidade e do nível de ecotoxicidade de xenobióticos à organismos.…”
Section: Experimento De Exposição Agudaunclassified